The Effect of Red Guava Juice (PsidiumGuava L.) on Lipid Profile Levels In Serum (Peer Reviewer) - Shahrul Rahman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Cardiovascular disease is the highest cause of death in most developing countries. The increased cholesterol is the main cause of coronary heart disease and fatty liver disease which increases the load / burden of both diseases. One of the alternative that can decrease the cholesterol levels in long term blood plasma is using the natural ingredients such as guava fruit which is known to contained flavonoid as antioxidant that can inhibit LDL oxidation so that the levels of LDL can be decreased and atherosclerosis can be prevented as well